TAT TWAM ASI DAN SOLUSI MASALAH STUDY CHANDOGYA UPANISAD - Tika, Putu Dian (JURNAL YOGA DAN KESEHATAN, 2019)
Mahavakya tat twam asi is contained in the chandogya upanisad 6.8.7 ?which means: you  are    it; You are all that; All beings are You. You are the beginning of jiwatman (spirit) and substance (prakrti) of all beings. Therefore my soul and your soul are single with the soul of all beings, and you are my source and the source of all beings. Therefore I am you, and vice versa. There are still a few Hindus who understand the meaning of Tat Twam Asi. Even though Tat Twam Asi is the Teachings of the similarity of Human Dignity or the Teachings of the Brotherhood. True, indeed all humans are brothers and sisters as a big family of the world, because the Atman of every human being is the same, namely the spark of the divine light of the Almighty God. Therefore there is also interpreting Tat Twam Asi as my Atman is your Atman, on the contrary your Atman is my Atman but there are also those who interpret Tat Twam Asi as the Doctrine of Compassion, where a large number of human beings must love one another, help each other and sharpen each other, love each other and fostering each other, so that life and human life become harmonious, safe, peaceful and peaceful.